2013
DOI: 10.3390/md11124876
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Cancer Preventive Properties of Marine Polysaccharides: Some Results and Prospects

Abstract: Many marine-derived polysaccharides and their analogues have been reported as showing anticancer and cancer preventive properties. These compounds demonstrate interesting activities and special modes of action, differing from each other in both structure and toxicity profile. Herein, literature data concerning anticancer and cancer preventive marine polysaccharides are reviewed. The structural diversity, the biological activities, and the molecular mechanisms of their action are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(78 citation statements)
references
References 154 publications
(171 reference statements)
3
67
0
2
Order By: Relevance
“…Jayamadhuri and Krishna (2013) isolated actinomycete strains from a tidal zone, and reported that actinomycete extracts had cytotoxic effects on the growth of breast cancer cell lines [20]. Fedorov conducted a study on marine actinomycetes in 2013 and reported that actinomycetes had a great potential in the treatment of cancer consistent with the result of the present study [21]. Ravikumar et al, (2012) reported that the anti-cancer property of cell-free extracts from actinomycete isolates might be due to the presence of the active secondary metabolites such as alkaloids and quinines [14].…”
Section: Discussionsupporting
confidence: 74%
“…Jayamadhuri and Krishna (2013) isolated actinomycete strains from a tidal zone, and reported that actinomycete extracts had cytotoxic effects on the growth of breast cancer cell lines [20]. Fedorov conducted a study on marine actinomycetes in 2013 and reported that actinomycetes had a great potential in the treatment of cancer consistent with the result of the present study [21]. Ravikumar et al, (2012) reported that the anti-cancer property of cell-free extracts from actinomycete isolates might be due to the presence of the active secondary metabolites such as alkaloids and quinines [14].…”
Section: Discussionsupporting
confidence: 74%
“…Additional chemical modifications could be explored to further improve the activity of BGF. Developing saccharide mimetics for in vivo applications is possible and might be explored in the future as well for the Lewis Y analogue BGF or similar compounds [18]. A particularly interesting aspect is that Lewis Y inhibitors will not serve as universal angiogenesis inhibitors but rather show selectivity for pathophysiological situations with TNF-alpha over expression which is known e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, microalgae are almost an untapped resource of natural antioxidants due to their enormous biodiversity, much more diverse than higher plants. They contain various biologically active compounds that are been used as source of food, feed and medicine [7] . Microalgae are proposed as an alternative molecular pharming system.…”
mentioning
confidence: 99%
“…Antioxidants are presumed to have several positive health effects that include prevention of cardiovascular disorders, ageing related diseases such as Alzheimer and certain types of cancer [10] . Microalgae in this regard are exceptionally rich source of pharmacologically active metabolites with antineoplastic, antitumor, antibacterial, antifungal and antiviral properties [7] .…”
mentioning
confidence: 99%